Ekonomi Keluarga Lewat UMKM: Kiprah IRT di Desa Karave Kabupaten Pasangkayu - Putri, Bella Octaviana; Parinding, Kalvin A.; Syamsuddin, H.; Suirlan, Rita; Paembonan, Laendatu (Transpublika Publisher, 2025)
This study aims to examine in depth the impact of mothers' involvement in MSMEs on family economic conditions and the role of mothers who are MSME entrepreneurs in shaping social change in the Karave village community. This study is descriptive in nature, with the aim of describing and analysing the contribution of micro, small and medium enterprises (MSMEs) run by housewives to increasing family income in Karave Village, Pasangkayu Regency. Based on the results of research in Karave Village, it can be concluded that mothers play an active role in increasing family income through micro-business activities, particularly in the culinary sector. Housewives are also able to become economic actors who support the stability and financial sustainability of their families. The data shows that most housewives who are MSME entrepreneurs earn an income above IDR 2,200,000, with a total of 9 respondents. Meanwhile, only 2 people are in the middle income category (IDR 1,500,000–IDR 2,200,000), and 4 people are in the low income category (less than IDR 1,500,000). These findings indicate variation in income, but the majority of respondents have been able to generate a fairly high income from their businesses. Overall, the contribution of housewives to family income reaches 79.50 per cent. Village governments and related agencies are advised to continue supporting and empowering housewives who are MSME entrepreneurs through training in entrepreneurship, business management, and financial management.